Field visit and workshop report: Defining the problem domain and identifying possible entry point for experiential learning intervention to support lantana management and landscape restoration in Mandla, Madhya Pradesh, India - Bell, Andrew R.; Sanil, Richu; Acharya, Pradyumna; Rakh, Pradeep; Hettiarachchi, Upeksha; Zhang, Wei (International Food Policy Research Institute, 2025)
The management of Lantana camara, an invasive plant species, is a major challenge across India. Its rapid spread across forests and adjoining agricultural lands has negatively affected biodiversity, reduced the availability of nontimber forest products (NTFPs), and rendered areas of agricultural land uncultivable. Invasive species management has become a national priority, and is reflected in goals in India’s Strategic Plan for Biodiversity, as the unchecked growth of Lantana affects landscapes across the country. In the Mandla District, in Madhya Pradesh, Lantana has decreased wildlife habitats and reduced fodder availability by replacing native grasses. This affects food security and livelihoods in the area, with disproportionate impacts on women who are responsible for collecting NTFPs, fuelwood and fodder from forests. As Lantana encroaches further, women must travel longer distances and spend more time gathering forest resources, which increases risk of human or wildlife attacks. Current by-laws in place promote collective action for eradication of Lantana and evidence shows that community-based management of Lantana can lead to positive social and ecological outcomes.